CYLD negatively regulates transforming growth factor-β-signalling via deubiquitinating Akt - Lim, Jae Hyang (Nature Pub. Group, 2012)
Lung injury, whether induced by infection or caustic chemicals, initiates a series of complex wound-healing responses. If uncontrolled, these responses may lead to fibrotic lung diseases and loss of function. Thus, resolution of lung injury must be tightly regulated. The key regulatory proteins required for tightly controlling the resolution of lung injury have yet to be identified. Here we show that loss of deubiquitinase CYLD led to the development of lung fibrosis in mice after infection with Streptococcus pneumoniae. CYLD inhibited transforming growth factor-β-signalling and prevented lung fibrosis by decreasing the stability of Smad3 in an E3 ligase carboxy terminus of Hsc70-interacting protein-dependent manner. Moreover, CYLD decreases Smad3 stability by deubiquitinating K63-polyubiquitinated Akt. Together, our results unveil a role for CYLD in tightly regulating the resolution of lung injury and preventing fibrosis by deubiquitinating Akt. These studies may help develop new therapeutic strategies for preventing lung fibrosis.